An empirical investigation into the impact of real exchange rate misalignment on economic performance: The case of Ghana. - ACHEAMPONG, PRINCE (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partialfulfillment Of The Requirements For The Award Of A Master Of Philosophy Degree In Finance.